Disfunção sexual e qualidade de vida em mulheres com fibromialgia - FERRO, Letácio Santos Garcia (2022)
Introduction: Fibromyalgia is a disease with a wide spectrum of symptoms associated with generalized pain, fatigue, cognitive and sleep disorders. It has a high prevalence of sexual dysfunction, which negatively affects quality of life and is associated with neuroendocrine factors, but these have not been elucidated. This study aims to investigate sexual dysfunction, total testosterone, 25-hydroxyvitamin D levels, and their relationship with quality of life. Methods: Cross-sectional study with women with chronic pain treated as outpatients. Diagnosis of the disease was confirmed, and quality of life was assessed by use of the Fibromyalgia Impact Questionnaire and sexual dysfunction by the Female Sexual Function Index. Serum levels of total testosterone and vitamin D were also measured. Results: There were 120 women studied with a mean age of 45.55 ± 10.43 years. 60% were married or living in a committed relationship and only 45% had completed high school. The mean fibromyalgia symptom scale score was 24.25 ± 4.28. The Fibromyalgia Impact Questionnaire had a mean score of 74.19 ± 14.97. Regarding sexual function, the mean index of sexual function in women was 10.01 ± 8.6, with 95.9% of patients having a score of 26 or less, suggestive of sexual dysfunction. A significant difference was found in the Fibromyalgia Impact Questionnaire between the groups with and without sexual dysfunction, with mean scores of 74.85 ± 14.32 and 58.93 ± 22.98, respectively. In the evaluated patients, 90.0% of the total had low levels of testosterone as well as in the entire age group studied and 88% had normal vitamin D levels. The Fibromyalgia Impact Questionnaire showed a moderate correlation with the Fibromyalgia Symptoms Scale and a high correlation with its domains, and the Female Sexual Function Index showed a negative correlation with age. There was no correlation between testosterone and the Female Sexual Function Index or vitamin D and the Fibromyalgia Impact Questionnaire. Conclusion: In women with fibromyalgia, changes in sexual function and deterioration in quality of life were observed, with no association with testosterone and vitamin D levels. The disease proved to be of high severity and affected young and active women who have less access to education and information. Therefore, patients need to be further monitored in the development of all these dysfunctions and associated symptoms.